Perspective-Taking and Empathy Mitigate Family-of-Origin Risk for Electronic Aggression Perpetration Toward Dating Partners: A Brief Report - Ramos, Michelle C. (Journal of interpersonal violence, 2021)
Electronic dating aggression among emerging adults is prevalent and has adverse consequences, yet factors that increase or decrease the risk for perpetrating electronic aggression against a romantic partner are understudied. This investigation advances the literature in two novel ways. First, based on intergenerational transmission of violence theories, we tested the link between family-of-origin aggression (FOA) history and electronic aggression toward romantic partners, using a diverse sample of emerging adults. Second, we examined whether perspective-taking and empathy each moderated the association between FOA and electronic dating aggression and explored the moderating role of gender. Participants included 359 undergraduate students (50% female; 42% White) from an urban university. Results indicated that greater FOA during childhood was associated with perpetrating greater electronic aggression against romantic partners. Furthermore, significant interactions indicated that perspective-taking and empathy separately buffered these associations. Youth from aggressive families did not exhibit increased electronic dating perpetration when they had higher perspective-taking or empathy. Males were especially sensitive to the protective effects of perspective-taking. Findings highlight potential points of intervention (i.e., cognitive and affective empathy training) to decrease electronic aggression in romantic relationships and break intergenerational cycles of aggression.